2021
DOI: 10.1016/j.watres.2020.116793
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic: Water, sanitation and hygiene (WASH) as a critical control measure remains a major challenge in low-income countries

Abstract: Highlights Effective WASH is necessary in the control of SARS-CoV-2 infection WASH situation in in low income countries is still inadequate for effective control of SARS-CoV-2 infection Proper Awareness on effective WASH is required under the current SARS-CoV-2 outbreak Detection of viral particles in faces, urine and wastewater could serve as early warning on SARS-CoV-2 infection trend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 65 publications
1
75
0
1
Order By: Relevance
“…Overall, these findings suggest that investments in WASH infrastructure, such as a piped water supply, not only ensure individuals have an enabling environment to perform promoted WASH practices but may also play a role in building the resilience of rural communities against future disease outbreaks. The findings also support the recommendations of Donde et al 35 that WASH is central to the COVID-19 response and recovery strategy and deserves sufficient funding to provide and maintain adequate WASH services in low- and middle-income countries.…”
Section: Discussionsupporting
confidence: 84%
“…Overall, these findings suggest that investments in WASH infrastructure, such as a piped water supply, not only ensure individuals have an enabling environment to perform promoted WASH practices but may also play a role in building the resilience of rural communities against future disease outbreaks. The findings also support the recommendations of Donde et al 35 that WASH is central to the COVID-19 response and recovery strategy and deserves sufficient funding to provide and maintain adequate WASH services in low- and middle-income countries.…”
Section: Discussionsupporting
confidence: 84%
“…Fair allocation of resources in the WASH organizations could include responding to the pandemic COVID-19. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Fair allocation of resources in the WASH organizations could include responding to the pandemic COVID-19. 37 The present pandemic of COVID-19 causes an additional challenge to the quality and safety of laboratory diagnosis testing, 38 and in HCF due to the generation of more waste than usual. 20 In this pandemic time, HCF produces wastes like gloves, masks, and other PPE that could be infected with the virus.…”
Section: Impacts Of Covid-19 On Wash Servicesmentioning
confidence: 99%
“…Raupp et al (2020) reported that the gap related to basic sanitation infrastructure between Indigenous and non-Indigenous households increased between 2000 and 2010 [ 39 ]. Access to clean water and sanitation is critical for preventing the spread of COVID-19 and other infectious diseases, which remain a major cause of mortality among Indigenous Brazilians [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%